Testing the Usability of a Mobile Learning Module - Mustafa, Nawal; Mohd Nordin, Norazah; Amin Embi, Mohamed; Helmi Norman, Mohd (International Journal of Engineering and Technology, 2018)
Healthcare professionals require skills and knowledge training in order to provide the best services. However, a heavy workload and time constraints have contributed to their reluctance to attend English communication training. Thus, a mobile learning module for continuing professional development has been developed but its usability evaluation would determine if the module will be used by its intended learners. This study aimed to evaluate the usability level of an English Communication Skills mobile module for healthcare professionals using FRAME modelâ€™s device, learner and social aspects of evaluation. 116 healthcare professionals evaluated the moduleâ€™s usability in a survey questionnaire while five participants were selected to be interviewed. Findings showed a high level of usability and interest to learn in a collaborative learning environment. This usability evaluation would be able to determine userâ€™s adoption of a mobile learning approach in a continuous professional development course and would benefit organisations when considering the most suitable mode of training for their employees. Recommendations for further study include assessing the effectiveness of the mobile learning module in developing communication skills among healthcare professionals. Â